2017
DOI: 10.1007/s11199-017-0742-2
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Involvement in Cyber Bullying and Perceptions of School: The Importance of Perceived Peer Acceptance for Female Adolescents

Abstract: Young people are spending increasing amounts of time using digital technology and, as such, are at great risk of being involved in cyber bullying as a victim, bully, or bully/victim. Despite cyber bullying typically occurring outside the school environment, the impact of being involved in cyber bullying is likely to spill over to school. Fully 285 11- to 15-year-olds (125 male and 160 female, M age = 12.19 years, SD = 1.03) completed measures of cyber bullying involvement, self-esteem, trust, perceived peer ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Cyberbullying is associated with some psychological, social, educational, health and family problems that extend to those involved in the phenomena [3,[14][15][16][17][18]. However, at a greater extent, cybervictims may suffer discrimination among peers, depression, aggressiveness, anxiety, fear, somatic disorders, deterioration of self-esteem, academic problems, substance use, and suicidal attempts and ideation [15,17,19,20].…”
Section: Cyberbullyingmentioning
confidence: 99%
“…Cyberbullying is associated with some psychological, social, educational, health and family problems that extend to those involved in the phenomena [3,[14][15][16][17][18]. However, at a greater extent, cybervictims may suffer discrimination among peers, depression, aggressiveness, anxiety, fear, somatic disorders, deterioration of self-esteem, academic problems, substance use, and suicidal attempts and ideation [15,17,19,20].…”
Section: Cyberbullyingmentioning
confidence: 99%
“…Over the last two decades, the number of adolescents who communicate through the internet has surged, carrying with it the increased risk of being involved in cyberbullying [2][3][4]. This form of violence is linked to serious social, psychological, educational, and health problems for everyone involved [3,[5][6][7][8], but it is the victims who suffer most, with social exclusion, profound depression, the use of addictive substances, or the ideation and attempts or consummation of suicide among the most serious consequences [9,10]. In addition, cyberbullying threatens the achievement of the Sustainable Development Goals.…”
Section: Introductionmentioning
confidence: 99%
“…The more adolescents engage in cyber aggression, the more loneliness they feel, the lower self-worth is, the fewer mutual friendships they have, the fewer the ratings of social acceptance and popularity by peers are. These consequences, in turn, reduce the perception of learning and school for cyberbullies (Betts, Spenser, & Gardner, 2017;Jacobs, Völlink, Dehue, & Lechner, 2014). Ybarra and Mitchell (2004) reported that 34.7% of aggressor-only youth showed problem behavior, 27.8% had low school commitment, 46% indicated cigarette or alcohol use, and 10.2% were severely depressed.…”
Section: Mental Health Problems Caused By Teenage Students' Cyberbullyingmentioning
confidence: 99%
“…They could recover from the negative effects faster (Fridh, Lindström, & Rosvall, 2015;Sakellariou, Carroll, & Houghton, 2012). Girls who had experienced cyberbullying had a negative impact on their learning outlook and school value, and were more likely to truancy and took a negative attitude towards school (Betts, Spenser, & Gardner, 2017). However, when faced with cyberbullying, girls are more likely than boys to seek social support for respect, understanding, and a sense of social belonging (Fridh, Lindström, & Rosvall, 2015).…”
Section: Relationship Between Gender Difference and Teenage Students' Cyberbullyingmentioning
confidence: 99%